Aplikasi Pembelajaran Interaktif Pada Pusat Pengembangan Anak GMIM Bait-El Bahu Manado - Alfando Excelsis Deo Sulangi; Virginia Tulenan; Nancy J. Tuturoong (Universitas Sam Ratulangi, 2025)
Abstract — Interactive learning is a means to make it easier for children to understand, understand and practice, so that the goals of the learning process can be achieved well. Interactive learning media is one component of supporting teaching and learning for both teachers and children. The interactive learning application at the Child Development Center aims to enable children to easily understand and know the 5 (five) main learning materials at the GMIM Bait-El Bahu Manado Child Development Center. This research aims to help children know the simple steps and functions of the 5 main materials, namely: eyes, nose, ears, tongue and skin. This application was created using the Multimedia Development Life Cycle (MDLC) method which consists of 6 stages, namely concept, design, material collection, creation, testing and distribution. This research produces an Android-based media application, namely an interactive learning application at the GMIM Bait - El Bahu Manado child development center for learning for children aged 3-5 years. After testing the application on respondents, the conclusion obtained in this application was that respondents were interested in using interactive learning applications as learning media in class, 100% answered